An EOQ model for deteriorating products with backorder and fixed transportation cost. Issue 1 (March 2021) - Girija Bai, H.; Mohamed Ismail, A.; Kaviya, D.; Muniappan, P.
Abstract: This paper deals buyer-vendor EOQ Inventory model for deteriorating product with fixed transportation cost. Optimum technique is used to find optimum order quantity and also developed for equal benefits of both buyer-vendor with co-ordination system. In order to reduce the total inventory cost, optimum order quantity and backorder levels are determined. We develop a production inventory model with screening and disposed cost for deteriorating products. shortages are not allowed in the inventory system. The buyer takes decision(disposed or screened)for damaged product. The proposed model is illustrated through numerical models.